IMPLEMENTASI PERENCANAAN PEMBELAJARAN OLEH GURU PAI POLA PEMBELAJARAN DARING BERDASARKAN KURIKULUM 2013 DI SMAN 1MALANG - Deajeng Putri Devi; Anwar Sa’dullah; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
There are many problems in various field with the development of this era, especially aducation. The pandemic period changed all arrangements in the learning system, found many obstacles and problems in learning. One of them is change in the mechanics of the implementation of learning, which was originally carried out in schools, is now carried out online or remotely through an agreed platform. The learning process can be said to be successful if the planning is designed as well and systeatically as possible. It is quite impressive for teachers to plan online pattern learning which later must relly be applied to students according to the objectives, moreover PAI subjects do not only talk about knowledge but attitudes will be more important in the learning objectives. State high school 1 Malang is the top ten best high schools in the academic field, of course it will be an axample for others as to what learning planning is wrapped up to produce good learning so as to give birth to students who are still able to complete during te Covid-19 pandemic. Apart from various obstacles and support in making lesson plans, teachers and students and even all actors in schools must be able to collaborate and harmonize online learning